Alternative Objective Functions for Firms. (September 2018) - Lankoski, Leena; Smith, N. Craig
The predominant view of the role of business in society is that the objective of business is to maximize profit. Some argue that it ought to be something different. Others argue that for many firms it already is something different. However, the "something different" has not been fully fleshed out in its various versions. To address this gap, we define different relationship types between variables in an objective function and develop and present the resulting range of 10 alternative objective functions for firms. We then discuss how their development contributes to conceptual, empirical, and normative debates about organizational purpose. Removing the conventional assumption of profit maximization as the sole management principle opens up the possibility of new, more nuanced theoretical approaches to management. This article lays the groundwork for such theory development through the systematic and analytical identification of alternative objective functions that represent different specifications of firm purpose.